DETERMINATION OF THE DAMAGED ZONE IN QUARRIES, RELATED TO AGGREGATE PRODUCTION - Jern M. (My University, 2001)
To make quarrying profitable, the blasting should effectively disintegrate the rock mass whilst at the same time minimising damage to the individual rock fragments. The zone of damage around blast holes has been considered in two quarries: in Permian dolerite at Billingsryd and tonalitic gneiss at Angered Quarry. The paper describes the fracture mapping and ultrasonic measurements undertaken.
Keywords: BLASTING; DAMAGE; ULTRASONIC; THIN SECTIONS; AGGREGATES; Permian; Paleozoic::Permian; Палеозой::Пермская